2021
DOI: 10.1109/tgrs.2020.3046004
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Intensity-Based Selection of Training Samples for Remote Sensing Building Damage Classification

Abstract: Previous applications of machine learning in remote sensing for the identification of damaged buildings in the aftermath of a large-scale disaster have been successful. However, standard methods do not consider the complexity and costs of compiling a training data set after a large-scale disaster. In this article, we study disaster events in which the intensity can be modeled via numerical simulation and/or instrumentation. For such cases, two fully automatic procedures for the detection of severely damaged bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…While transfer learning remains difficult for complex deep-learning models, the transfer of simpler models, or the use of supervised expert knowledge within unsupervised frameworks, remains an interesting research lead. In this regard, the work of Moya et al on fragility functions and the demand parameter depending on the disaster intensity and partial field information seems to be promising [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While transfer learning remains difficult for complex deep-learning models, the transfer of simpler models, or the use of supervised expert knowledge within unsupervised frameworks, remains an interesting research lead. In this regard, the work of Moya et al on fragility functions and the demand parameter depending on the disaster intensity and partial field information seems to be promising [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In [15], the authors use the same combination of a fragility function with a machine learning method, this time with Support Vector Machines. They also introduce the demand parameter using various thresholding techniques and field information from in situ sensors, which allow to better define high-priority areas.…”
Section: Ai Based On Semi-supervised Learningmentioning
confidence: 99%
“…Remote sensing data have been used to extract information from urban and rural areas, such as land cover classification (Geiß et al, 2020), urban growth (Shi et al, 2019), and detection of damaged buildings (Moya et al, 2021). Regarding informal settlements, a comprehensive study of its spatial morphology can be found in Taubenböck et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of RS Earth observation imagery and its free availability has meant that monitoring of changes following disasters has turned into a hot topic for research [21][22][23][24][25][26][27][28]. Indeed, we are witnessing many BAM products on a global scale that differ in terms of spatial resolution and reliability of the burned areas mapped.…”
Section: Introductionmentioning
confidence: 99%